(untitled) (TANMIYAT AL-RAFIDAIN, 2026)
Despite the significant tourism potential of the Kurdistan Region of Iraq, its international presence remains limited, creating a clear research gap on how social media effectively influences the travel decisions of foreign tourists. Accordingly, this study addresses the main research question: To what extent do social media influence the attractiveness of the Kurdistan Region of Iraq for international tourists? This study was conducted with an applied purpose and a descriptive survey methodology. Primary data were collected from 384 international tourists visiting Erbil during peak tourism periods using a structured and pre-validated questionnaire. Convenience sampling was used, and the instrument demonstrated acceptable reliability, with Cronbach’s alpha coefficients exceeding 0.80. Statistical analyses, including descriptive statistics, normality assessment, and a one-sample t-test, were performed using SPSS software. The results show that social media has a statistically significant and positive impact on international tourist attractions (t > 1.96, p < 0.05). Among the components analyzed, the quality of visual content, user-generated comments, and targeted social media advertising were identified as the most influential determinants of tourist perceptions and travel intentions. Among the limitations of the fieldwork were limited tourist access to certain locations and seasonal variations in visitor numbers, which affected the stability of participants’ access. The study recommends developing culturally appropriate digital marketing strategies, enhancing multilingual social media content, and strengthening professional management of online tourism campaigns to enhance the region’s global digital presence. This research contributes to filling the limited knowledge base on emerging tourism destinations and provides practical insights for policymakers and tourism stakeholders seeking to increase international tourist arrivals.